2015
DOI: 10.1002/jmri.24843
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐weighted imaging in assessing pathological response of tumor in breast cancer subtype to neoadjuvant chemotherapy

Abstract: DWI appears to be a promising tool to determine the association of pathological response to NAC in breast cancer subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 28 publications
2
50
0
Order By: Relevance
“…Additionally, pretreatment ADC measures may hold prognostic value to help identify patients who will best respond to neoadjuvant treatments. Three large scale studies of women with locally advanced breast cancer undergoing neoadjuvant chemotherapy (n = 519 women total) each showed low pretreatment tumor ADC values to be predictive of pathological complete response for triple‐negative tumors, with more variable findings in luminal and HER2 + subtypes . However, there is wide variability in the current literature as to the utility of DWI to monitor breast cancer therapy, likely due to differences in study design (including treatment timings of imaging, patient characteristics, and ADC measurement approaches), and further investigation is needed to validate ADC as a predictive biomarker of therapeutic efficacy.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Additionally, pretreatment ADC measures may hold prognostic value to help identify patients who will best respond to neoadjuvant treatments. Three large scale studies of women with locally advanced breast cancer undergoing neoadjuvant chemotherapy (n = 519 women total) each showed low pretreatment tumor ADC values to be predictive of pathological complete response for triple‐negative tumors, with more variable findings in luminal and HER2 + subtypes . However, there is wide variability in the current literature as to the utility of DWI to monitor breast cancer therapy, likely due to differences in study design (including treatment timings of imaging, patient characteristics, and ADC measurement approaches), and further investigation is needed to validate ADC as a predictive biomarker of therapeutic efficacy.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…First, pre-treatment ADC measures may improve prognostic ability to identify which patients will best respond to neoadjuvant treatments. In women with triple-negative disease (ER, PR, and HER2-negative) undergoing neoadjuvant chemotherapy, several large studies have observed low pre-treatment tumor ADC values to be associated with pathological complete response [36, 45, 46]. Second, post-treatment DWI may provide a means to accurately assess extent of residual disease prior to surgery.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…4244 The predictive value of ADC has been shown to be further strengthened based on breast cancer subtype stratification. 76,77 …”
Section: Emerging Strategiesmentioning
confidence: 99%